Impact of high soot-loaded and regenerated diesel particulate filters on the emissions of persistent organic pollutants from a diesel engine fueled with waste cooking oil-based biodiesel. (1st April 2017) - Chen, Chia-Yang; Lee, Wen-Jhy; Wang, Lin-Chi; Chang, Yu-Cheng; Yang, Hsi-Hsien; Young, Li-Hao; Lu, Jau-Huai; Tsai, Ying I.; Cheng, Man-Ting; Mwangi, John Kennedy
Graphical abstract: Highlights: WCO-based biodiesel blends cannot stimulate POPs formation in uncatalyzed DPF. Formation mechanism of POPs in diesel engines is homogeneous gas-phase formation. The gas-phase POPs are highly dominant in the raw exhausts of diesel engines. The regeneration of the DPF can drastically reduce the formation potential of POPs in the DPFs. Abstract: This study evaluated the impact on persistent organic pollutant (POP) emissions from a diesel engine when deploying a diesel oxidation catalyst (DOC) combined with an uncatalyzed diesel particulate filter (DPF), as well as fueling with conventional diesel (B2) and waste cooking oil-based (WCO-based) biodiesel blends (B10 and B20). When the engine was fueled with WCO-based biodiesel blends (B10 and B20) in combination with deploying DOC+A-DPF, their levels of the chlorine and potassium contents could not stimulate the formation of chlorinated POPs (PCDD/Fs and PCBs), although previous studies had warned that happened on diesel engines fueled with biodiesel and deployed with iron-catalyzed DPFs. In contrast, the WCO-based biodiesel with a lower aromatic content reduced the precursors for POP formation, and its higher oxygen content compared to diesel promoted more complete combustion, and thus using WCO-based biodiesel could reduce both PM2.5 and POP emissions from diesel engines. This study also evaluated the impact of DPF conditions on the POP emissions from a diesel engine; that is, the difference in POP emissions before and just after the regeneration of the DPF. In comparison to the high soot-loaded DPF scenario, the regeneration of the DPF can drastically reduce the formation potential of POPs in the DPFs. An approach was developed to correct the effects of sampling artifacts on the partitioning of gas- and particle-phase POPs in the exhaust. The gas-phase POPs are highly dominant (89.7–100%) in the raw exhausts of diesel engines, indicating that the formation mechanism of POPs in diesel engines is mainly through homogeneous gas-phase formation, rather than de novo synthesis.